Sosialisasi untuk Guru Sosiologi di Malang Raya dalam Menyusun Desain Pembelajaran - Pratiwi, Seli Septiana; Fibrianto, Alan Sigit; Meiji, Nanda Harda Pratama; Apriyadi, Deny Wahyu (Universitas Dinamika, 2025)
Learning desain is evidence of the teacher’s readiness to carry out their teaching duties in the classroom. Through good learning design, learning activities will encourage students to be more active and achieve learning objectives. Therefore, teachers need to have the ability to design learning that suits the needs of students. Activities to improve the ability of sociology teachers to design learning aim to create learning conditions that are in line with the needs of students. This activity increases the opportunity to develop effective and efficient learning conditions according to the characteristics of students and school facilities. The stages of the activity are divided into three, namely planning, implementation, and evaluation. In the planning activity, coordination was carried out with the community namely MGMP Sosiologi in Malang Raya and East Jawa in SMA and MA as activity partners. In addition, with the involvement of MGMP, information was obtained on urgent needs from sociology teachers, especially in Malang Raya. The implementation mechanism in divided into two, namely offline and online. Online activities are divided into two sessions discussing learning achievements and innovative learning models. The offline session discusses assessment, preparation of teaching modules, and understanding by design. The evaluation results show that the majority of participants get a good impact from the activities such as understanding the material and experience received during the activities from the methods used by the speakers. Based on the training results, teacher are encourage to be able to desaign learning according to the applicable curriculum.